Answer:
sept 30
Step-by-step explanation:
Answer:
36 is the final value for the equation you posted
Step-by-step explanation:
We are told that = 3 and = −2.
Let's plug these values into the equation.
= (5 ( − 2) + (2 − )^2)
= (5 (3 − 2(−2)) + (2 − 3)^2)
= (5 (3 + 4) + (−1)^2)
= (5 (7) + 1)
= 35 + 1
= 36
Answer:
Step-by-step explanation:
Total for football: 9 +7
Total for figure skating: 12 +7
NEW Total for football: 16
NEW Total for figure skating: 19
The question says that 9 people like football
The question says that 12 people like to watch figure skating
The question also says that 7 people like to watch both, and because of that, you should add 7 to both 9 and 12, but keep the new numbers separated from each other. So once we know the sum of 9 +7 is 16, and 12 + 7 is 19, we can subtract the two numbers, and get 3 as the answer. Because you are counting the number of times that you have to travel up or down to the other number, and so if you are on a set of stairs that go up to the 16 level and you are on the 14th level, you need to travel up 2 sets of stairs to get to level 16.
Hope that example helps and can help in the future with other problems!
Answer:
(2x-1)(2x+1)(x^2+2) = 0
Step-by-step explanation:
Here's a trick: Use a temporary substitution for x^2. Let p = x^2. Then 4x^4+7x^2-2=0 becomes 4p^2 + 7p - 2 = 0.
Find p using the quadratic formula: a = 4, b = 7 and c = -2. Then the discriminant is b^2-4ac, or (7)^2-4(4)(-2), or 49+32, or 81.
Then the roots are:
-7 plus or minus √81
p= --------------------------------
8
p = 2/8 = 1/4 and p = -16/8 = -2.
Recalling that p = x^2, we let p = x^2 = 1/4, finding that x = plus or minus 1/2. We cannot do quite the same thing with the factor p= -2 because the roots would be complex.
If x = 1/2 is a root, then 2x - 1 is a factor. If x = -1/2 is a root, then 2x+1 is a factor.
Let's multiply these two factors, (2x-1) and (2x+1), together, obtaining 4x^2 - 1. Let's divide this 4x^2 - 1 into 4x^4+7x^2-2=0. We get x^2+2 as quotient.
Then, 4x^4+7x^2-2=0 in factored form, is (2x-1)(2x+1)(x^2+2) = 0.
Answer:
1/14
Step-by-step explanation:
There is only 1 common multiple of 4 and 6 between 1 and 14.
So the probability is: